Low-Dose Prophylactic Oral Iron Supplementation (Ferrous Fumarate, Ferrous Bisglycinate, and Ferrous Sulphate) in Pregnancy Is Not Associated With Clinically Significant Gastrointestinal Complaints: Results From Two Randomized Studies - Nils Thorm Milman; Thomas Bergholt (Wiley, 2024)
Conclusion: Low-dose iron supplementation appears to have no clinically significant GI side effects, as none of the included women presented with GI complaints of such severity that it necessitated either reduction of iron dose, change to an alternative iron formula, or discontinuation of iron supplement. However, ferrous bisglycinate 25 mg iron/day is associated with significantly fewer GI complaints than ferrous fumarate 40 mg iron/day and ferrous sulphate 50 mg iron/day. Ferrous bisglycinate may be preferred for iron prophylaxis, especially in women experiencing GI side effects when taking other conventional iron formulas.